A probable fatal argon gas embolism during resection of a cutaneous biliary fistula - a case report - Powell,Karlyn (2020)
Abstract Background: The Argon Beam Coagulator (ABC) achieves hemostasis but has potential complications in the form of argon gas embolisms. Risk factors for embolisms have been identified and ABC manufacturers have developed guidelines for usage of the device to prevent embolism development. Case report: A 49 year-old male with history of recurrent cholangiocarcinoma status post resection presented for resection of a cutaneous biliary fistula. Shortly after initial use of the ABC, the patient underwent cardiac arrest. After resuscitation, air bubbles were observed in the left ventricle via Transesophageal Echo (TEE). Conclusion: Although argon embolisms have been described more commonly during laparoscopies, this patient most likely experienced an argon gas embolism during an open resection of a cutaneous biliary fistula via the biliary tract or vein with possible transpulmonary passage of the embolism. Consequently, a high degree of suspicion should be maintained for an argon gas embolism during ABC use in laparoscopic, open, and cutaneous surgeries.